A munkaerő-piaci előrejelzések nemzetközi gyakorlata: Áttekintés a kvantitatív módszerekről és felhasználásukról 12 ország és az Európai Unió előrejelzési tapasztalatai alapján - János Gács; Anikó Bíró (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– The study presents a comprehensive overview of labour market forecasting activities, mostly quantitative, based on multi-sector models, in 12 countries and the European Union. The principal aim of this effort is to provide ideas, lessons and benchmarks for similar forecasting exercises in Hungary. After outlining the basic model of quantitative labour market forecasting the paper identifies the technical conditions of model building and model quantification, as well as the characteristic features of organising the forecasting work. This analysis is based on cross-country comparative analysis and on the presentation of examples from the individual countries. In the following section the authors address the paths of improvement in the traditional forecasting model. Here the possibilities of substitution in terms of occupations and qualifications are discussed, and the difficulties of including the generic skills as a new variable in the forecasts. A section is devoted to the analytical tools that can be used after the forecasts are ready, such as the shift-share analysis and the IFLM-indicator that compares forecasted demand and supply in individual occupations or qualification categories. The discussion of estimated future labour market imbalances and the measured accuracy of the forecasts leads the authors to a fundamental issue of labour market forecasts, i.e. whether the results of the calculations can be considered forecasts proper for future developments, or they should be seen simply as well-informed, systematic projections? The second part of the study provides a detailed presentation of forecasting practices in the individual countries.
Keywords: E27; J11; J2; O41; 330; labour force requirement; labour supply; multi-sector models; forecasting; Arbeitsmarktprognose; Prognoseverfahren; Mehrsektoren-Modell; EU-Staaten; USA; Australien